A new machine for acquire pavement texture - Vilaça, João L. (2009)
This paper presents a prototype machine for the acquisition and characterization of the macrotexture and megatexture of road surfaces. The development stages of the prototype machine involved: 3D data acquisition system configuration and calibration - based on laser triangulation technique, 3D surface reconstruction of the road surface and texture characterization using appropriated indicators, such as the Mean Profile Depth (MPD) and the Texture Profile Level (L), by applying different and complementary mathematical techniques. The prototype machine created is able to work in laboratory and in field, allowing an acquisition accuracy of 0.5 mm. The contribution of this research is in developing a prototype machine capable of acquiring an extensive area road surface with high precision 3D data.